Method for determination of phthalate contents in PVC plastic toys using gas chromatography/mass spectrometry - Sriyotai, Woraprapa; Suwan, Duangnapa (Bulletin of Applied Sciences, 2022)
Method for determination of Phthalate; dibutyl phthalate (DBP), benzyl butyl phthalate (BBP), Di (2-ethylhexyl) phthalate (DEHP) and Di-n-octyl phthalate (DOP) in plastic toys was investigated by gas chromatography/ mass spectrometry using the modified method based on CPSC-CH-C-1001-09.03 prior to the use in routine work. The results showed that the linearity range of DBP, BBP, DEHP and DnOP was 0.02- 10 µg/mL, the detection limits of DBP, BBP, DEHP and DnOP was 0.01 %w/w, and the limits of quantitation of DBP, BBP, DEHP and DnOP was 0.02 %w/w. Percentage recovery of DBP, BBP, DEHP and DnOP by spike phthalate standard substance were 76-93, 125-129, 72-87 and 89-130 respectively. Range of percentage relative standard deviation was 1.1-7.4, which was within the acceptance range. Therefore, this method was fit for the intended use.